Mapping the landscape of organizational theories for future research themes in supply chain risk management - Cankaya, Sibel Yildiz; Saglam, Yesim Can; Sezen, Bülent (Emerald Group Publishing Ltd, 2023)
Purpose The aim of this conceptual study is to analyze the effects of state-of-the-art research streams on supply chain risk management (SCRM) based on organizational theoretical background and direct future research toward the use of other related organizational theories. This paper seeks to provide a framework for understanding various organizational theories that can impact the understanding of SCRM. Design/methodology/approach A systematic literature review on articles published from 1998 to 2020 was conducted manually in the following databases: Emerald, Science Direct, Taylor & Francis Online, and Wiley online library. Among these articles, the paper by Smeltzer and Siferd (1998) is the first article published on the topic. Therefore, that serves as a starting point for the papers' analysis. A total of 109 articles have been selected and reviewed in detail. Findings The results of the study indicate that the articles which utilize theories in SCRM research have been mostly published in the last three years. The quantitative and case studies have been prevalently applied methods in the articles. In total, 34 theories are listed from the investigated articles. The four commonly studied theories among these are the information processing theory, transaction cost theory, contingency theory, and resource-based view. Originality/value This paper is the pioneer in the sense that the paper specifically and directly reviews the SCRM literature in terms of organizational theory usage. For future research, this study offers a diffusion of innovation (DOI) theory that explains the factors which can affect the adoption or diffusion of SCRM practices.
Keywords: Supply chain risk management; Risk management; Organizational theory; Systematic literature review; Diffusion of innovation theory